BTG1 Expression Correlates with the Pathogenesis and Progression of Ovarian Carcinomas - Hua-Chuan Zheng (International Journal of Molecular Sciences, 2013)
BTG (B-cell translocation gene) can inhibit cell proliferation, metastasis, and angiogenesis and regulate cell cycle progression and differentiation in a variety of cell types. We aimed to clarify the role of BTG1 in ovarian carcinogenesis and progression. A BTG1-expressing plasmid was transfected into ovarian carcinoma cells and their phenotypes and related proteins were examined. BTG1 mRNA expression was detected in ovarian normal tissue (n = 17), ovarian benign tumors (n = 12), and ovarian carcinoma (n = 64) using real-time RT-PCR. Ectopic BTG1 expression resulted in lower growth rate, high cisplatin sensitivity, G1 arrest, apoptosis, and decreased migration and invasion. Phosphoinositide 3-kinase, protein kinase B, Bcl-xL, survivin, vascular endothelial growth factor, and matrix metalloproteinase-2 mRNA and protein expression was reduced in transfectants as compared to control cells. There was higher expression of BTG1 mRNA in normal tissue than in carcinoma tissue (p = 0.001) and in benign tumors than in carcinoma tissue (p = 0.027). BTG1 mRNA expression in International Federation of Gynecology and Obstetrics (FIGO) stage I/II ovarian carcinomas was higher than that in FIGO stage III/IV ovarian carcinomas (p = 0.038). Altered BTG1 expression might play a role in the pathogenesis and progression of ovarian carcinoma by modulating proliferation, migration, invasion, the cell cycle, and apoptosis.